Pension level, subjective wellbeing, and preference of care model among elderly people: An empirical study based on structural equation modeling - Chenyang Shao; Wenshun Li (Frontiers in Public Health, 2023)
The problem of population aging is becoming increasingly serious, and the elderly care model has become the social focus in China. It is urgent to improve the traditional home based elderly care model and increase the recognition of the residents for the socialized elderly care model. Based on the data of the 2018 China Longitudinal Aging Social Survey (CLASS), this paper uses structural equation model (SEM) to empirically test the impact of the elderly group's social pension level and subjective well–being on their choice of various care models. The results show that the improvement of elderly's pension level can significantly inhibit their choice of home–based care model, and promote their choice of community and institution care model. Subjective well–being can play a mediating role in the home–based and community care model choices, but the indirect approach mediated by subjective well–being only plays a supplementary role. In addition, the heterogeneity analysis shows that there are discrepancies in the impact and path for the elderly with different gender, age, household registration, marital status, health status, education level, number of children, and gender of children. The results of this study will help the improvement and development of social pension policy, optimizing the structure of residents' elderly care model and the process of “active aging”.